Assessment of the food-water-energy nexus suitability of rooftops. A methodological remote sensing approach in an urban Mediterranean area. (December 2021) - Zambrano-Prado, Perla; Muñoz-Liesa, Joan; Josa, Alejandro; Rieradevall, Joan; Alamús, Ramon; Gasso-Domingo, Santiago; Gabarrell, Xavier
Highlights: A framework to identify roofs for food, water, and energy production is proposed. Agriculture can be implemented on 8% of roofs to produce tomatoes and lettuce. A total of 87% of roofs are suitable for integrating rainwater harvesting systems. A total of 50% of roofs are suitable for integrating photovoltaic panels. Service buildings and residential housing are more suitable for agriculture. Abstract: This work established a framework to identify and analyze the technical feasibility of roofs for integrating urban agriculture, rainwater harvesting, and photovoltaic systems using various remote sensing. The framework was applied to a region north of Barcelona. Three levels of solar access requirements for tomatoes, leafy crops, strawberries, and microgreens were established. The case study included compact and disperse urban forms, residential and nonresidential building uses and various building typologies. It was identified that 8% of the roof area is feasible for tomato and lettuce production, and production could satisfy the 210% of average intake of tomatoes and the 21% average yearly consumption of lettuce. Rainwater harvesting systems could supply 94.26% of the water requirements for lettuce growing in an open-air system; in contrast, 53% of irrigation could be satisfied for tomato production in rooftop greenhouse systems. The results showed a potential for 80% of roof area to be used for rainwater harvesting systems, representing the average yearly water consumption of 44% of citizens for laundry, showering, toilet flushing, cleaning and irrigation uses. Finally, 50% of the roofs are suitable for photovoltaic panels, representing an average energy consumption of 18% of citizens.